Genetic Adjuvants in Replicating Single-Cycle Adenovirus Vectors Amplify Systemic and Mucosal Immune Responses against HIV-1 Envelope - William E. Matchett; Goda Baddage Rakitha Malewana; Haley Mudrick; Michael J. Medlyn; Michael A. Barry (Vaccines, 2020)
Most infections occur at mucosal surfaces. Providing a barrier of protection at these surfaces may be a useful strategy to combat the earliest events in infection when there are relatively few pathogens to address. The majority of vaccines are delivered systemically by the intramuscular (IM) route. While IM vaccination can drive mucosal immune responses, mucosal immunization at intranasal (IN) or oral sites can lead to better immune responses at mucosal sites of viral entry. In macaques, IN immunization with replicating single-cycle adenovirus (SC-Ads) and protein boosts generated favorable mucosal immune responses. However, there was an apparent “distance effect” in generating mucosal immune responses. IN immunization generated antibodies against HIV envelope (env) nearby in the saliva, but weaker responses in samples collected from the distant vaginal samples. To improve on this, we tested here if SC-Ads expressing genetic adjuvants could be used to amplify antibody responses in distant vaginal samples when they are codelivered with SC-Ads expressing clade C HIV env immunogen. SC-Ads env 1157 was coadministered with SC-Ads expressing 4-1BBL, granulocyte macrophage colony-stimulating factor (GMCSF), IL-21, or Clostridoides difficile (C. diff.) toxin fragments by IN or IM routes. These data show that vaginal antibody responses were markedly amplified after a single immunization by the IN or IM routes, with SC-Ad expressing HIV env if this vaccine is complemented with SC-Ads expressing genetic adjuvants. Furthermore, the site and combination of adjuvants appear to “tune” these antibody responses towards an IgA or IgG isotype bias. Boosting these priming SC-Ad responses with another SC-Ad or with SOSIP native-like env proteins markedly amplifies env antibody levels in vaginal washes. Together, this data may be useful in informing the choice of route of delivery adenovirus and peptide vaccines against HIV-1.